2017
DOI: 10.1080/14789949.2017.1280072
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating patterns of substance misuse by subtypes of antisocial traits in male offenders

Abstract: Among criminal offenders, two subtypes of antisocial traits, psychopathy and externalizing-only, are associated with an especially elevated risk for substance use disorders (SUDs). The present study examined the associations of these traits with patterns of substance misuse. In a sample of 1410 male offenders, we used diagnoses for alcohol, cannabis, opioids, and stimulants to examine the association between antisocial traits and SUD severity, as well as, age at substance use initiation. Results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Psychopathy can be conceptualized as a constellation of traits including callousness, interpersonal manipulation, egocentrism, and disinhibition (Cooke & Michie, 2001). These traits have shown consistent associations with a variety of negative outcomes such as proactive and reactive aggression, substance use behaviors, and institutionalization (Brennan, Stuppy-Sullivan, Brazil, & Baskin-Sommers, 2017; Hecht, Berg, Lilienfeld, & Latzman, 2016; Hemphill, Hare, & Wong, 1998).…”
mentioning
confidence: 99%
“…Psychopathy can be conceptualized as a constellation of traits including callousness, interpersonal manipulation, egocentrism, and disinhibition (Cooke & Michie, 2001). These traits have shown consistent associations with a variety of negative outcomes such as proactive and reactive aggression, substance use behaviors, and institutionalization (Brennan, Stuppy-Sullivan, Brazil, & Baskin-Sommers, 2017; Hecht, Berg, Lilienfeld, & Latzman, 2016; Hemphill, Hare, & Wong, 1998).…”
mentioning
confidence: 99%
“…Individuals with elevated psychopathic traits tend to display heightened patterns of alcohol and drug use, along with earlier onset of use, compared to those with lower trait levels (Corrado et al, 2004;Hemphill et al, 1994;Smith & Newman, 1990;Taylor & Lang, 2006;walsh et al, 2007). Studies in males have observed positive relationships between PCL-R Factor 2 (lifestyle-antisocial traits) and drug use (Brennan et al, 2017;Dargis et al, 2017;Hemphill et al, 1994;Mailloux et al, 1997;Smith & Newman, 1990;walsh et al, 2007). However, relationships between psychopathy and alcohol use in males have been somewhat mixed.…”
Section: Psychopathy and Substance Usementioning
confidence: 99%
“…However, psychopathic personality traits have been differentiated from global externalising behaviours. For example, the relationship between substance abuse and psychopathic personality traits versus externalising behaviours is best explained by distinguishing aspects of substance abuse: dependency severity is predicted by externalising behaviours but not psychopathic personality traits, whilst early onset of substance abuse is predicted by psychopathic personality traits but not externalising behaviours (Brennan et al, 2017).…”
Section: Externalising Behaviours and Aspects Of Psychopathymentioning
confidence: 99%